Progress on the nephrite sources of jade artifacts in ancient China from the perspective of isotopes - Wang, Rong; Shi, Xiaowei (Frontiers in Earth Science, 2022)
The use of isotopes is crucial for understanding the origin of jade/nephrite. This article first contrasts recent studies on the radioisotopes and stable isotopes of contemporary nephrite deposits in China, Baikal region, and South Korean Peninsula. It then reviews the isotopic analysis of the sources of nephrite artifacts in ancient China, highlighting the concentration of contemporary nephrite deposits with distinct isotopic fingerprints in three significant geographic areas, Northeast Asia, the Yellow River Basin, and South China Region. That is, with regard to Northeast Asia, S‐type and D‐type nephrite in Baikal region, and D‐type nephrite in Chuncheon of South Korea as well as Xiuyan and Kuandian of Liaoning Province can be distinguished well by the radioisotope mineralization age and hydrogen and oxygen isotopic values; with regard to the Upper Yellow River, the isotope method of hydrogen, oxygen and silicon isotopic values has the potential to distinguish the D-type and S-type nephrite in Xinjiang Province and Qinghai Province, while cannot distinguish the D-type nephrite from Hetian, Xinjiang Province and Lintao/Maxianshan, Gansu Province; with regard to South China, the isotope method of the radioisotope mineralization age and hydrogen and oxygen isotopic values has the potential to distinguish D-type nephrite from Fugong in Yunnan Province, Dahua in Guangxi Province and Luodian in Guizhou Province, and S-type nephrite in Hualian, Chinese Taiwan. It is recommended that isotopic database of jade materials from more deposits and excavated jadewares must be established, in order to answer significant archaeological questions regarding the role of jade material utilization in the origin, formation and development of Chinese jade culture and Chinese civilization.